180 ROLE OF CASPASE 2 IN APOPTOTIC SIGNALING OF PRIMATE MALE GERM CELLS. Issue 1 (1st January 2007) - Johnson, C.; Jia, Y.; Sinha Hikim, A. P.; Swerdloff, R. S.; Lue, Y. H.; Han, X.; Zhang, X. S.; Hu, Z. Y.; Li, Y. C.; Liu, Y. X.; Wang, C.
Abstract : Objective: Caspase 2 is an initiator caspase whose activation has been found to promote apoptosis through mitochondria-dependent intrinsic pathway signaling in various cell systems, including the oocyte. Previously, we have shown that the intrinsic pathway is the key pathway for male germ cell apoptosis in rodents, monkeys, and men. The present study investigates if germ cell apoptosis induced by mild testicular hyperthermia or deprivation of intratesticular testosterone (T) or after combined interventions involves activation of caspase 2. Study Design: Groups of eight adult cynomolgus monkeys received one of the following treatments: (1) two empty silastic implants (C); (2) two 5.5 cm-T implants (T); (3) daily exposure of testes to heat (43°C for 30 minutes) for 2 consecutive days (H); and (4) two T-implants plus exposure of the testes to heat for 2 consecutive days (H + T). Testicular biopsies were performed before and at 3, 8, and 28 days during treatment. Results: Mean incidence of germ cell apoptosis increased significantly by d 3 in the H-alone group and by d 8 in the T-alone group but peaked at d 3 in the H + T group. Maximum activation of caspase 2 in respective treatment groups, as evidenced by immunocytochemistry and immunoblotting using an active caspase 2 antibody, coincided with the increased incidence of apoptosis. In control testes, we detected moderate immunostaining for active caspase 2 in Sertoli cells with little or no expression of germ cells. In contrast, we found a strong staining for active caspase 2 in apoptotic germ cells and in the Sertoli cells Co-staining for TUNEL and active caspase 2 further confirmed activation of caspase 2 only in those germ cells undergoing apoptosis. Conclusion: Caspase 2 is activated in male germ cell apoptosis in nonhuman primates after heat stress, hormonal deprivation, or combined interventions. Future studies aimed at determining the expression of inhibitor of apoptosis proteins in testis will be needed to determine why Sertoli cells are not dying in spite of enhanced expression of caspase 2.